Diagnosed or prescribed only? A national analysis of initial evaluation and management of insomnia among older adult Medicare beneficiaries. Issue 1 (15th October 2021) - Wickwire, Emerson M; Jobe, Sophia L; Martin, Jennifer L; Williams, Scott G; Capaldi, Vincent F; Collen, Jacob; Doyinsola Bailey, M; Scharf, Steven M; Johnson, Abree; Albrecht, Jennifer S
Abstract: Study Objectives: To describe initial insomnia-related encounters among a national sample of Medicare beneficiaries, and to identify older adults at risk for potentially inappropriate prescription insomnia medication usage. Methods: Our data source was a random 5% sample of Medicare administrative claims data (2006–2013). Insomnia was operationalized as International Classification of Disease, Ninth Revision, Clinical Modification diagnostic codes. Insomnia medications included FDA-approved insomnia-related medication classes and drugs. Logistic regression was employed to identify predictors of being "prescribed only" (i.e., being prescribed an insomnia medication without a corresponding insomnia diagnosis). Results: A total of N = 60 362 beneficiaries received either an insomnia diagnosis or a prescription for an insomnia medication as their first sleep-related encounter during the study period. Of these, 55.1% ( n = 33 245) were prescribed only, whereas 44.9% ( n = 27 117) received a concurrent insomnia diagnosis. In a fully adjusted regression model, younger age (odds ratio (OR) 0.98; 95% confidence interval (CI) 0.98, 0.99), male sex (OR 1.15; 95% CI 1.11, 1.20), and several comorbid conditions (i.e., dementia [OR 1.21; 95% CI 1.15, 1.27] and anemia [OR 1.17; 95% CI 1.13, 1.22]) were positively associated with being prescribed only. Conversely, black individuals (OR 0.83; 95% CI 0.78, 0.89) and those of "other" race (OR 0.89; 95% CI 0.84, 0.94) were less likely to be prescribed only. Individuals who received care from a board-certified sleep medicine provider (BCSMP) were less likely to be prescribed only (OR 0.27; 95% CI 0.16, 0.46). Conclusions: Fewer than half of Medicare beneficiaries prescribed insomnia medications ever received a formal sleep-related diagnosis.